On the Seismic Response of the Faculty of Architecture and Engineering Building at Tohoku University. Issue 1 (February 2016) - Wang, Ying; Villalobos, Enrique; Pujol, Santiago; Al-Washali, Hamood; Suzuki, Kazuki; Maeda, Masaki; Takahashi, Susumu; Ichinose, Toshikatsu
The Faculty of Architecture and Engineering Building at Tohoku University survived two strong ground motions. This is not surprising because the structure was stiff and strong. What is surprising is that the first ground motion did not cause severe structural damage but the second one caused so much structural damage that the building had to be evacuated and demolished. The damage occurred despite two key facts: (1) the intensities of the mentioned ground motions are understood to have been similar and (2) the building was strengthened after the first motion (and before the second) following stringent standards.